MEDICAL WASTE MANAGEMENT IN GAZIANTEP - Aydogan, Oznur; Varank, Gamze; Bilgili, M. Sinan (YILDIZ TECHNICAL UNIV, 2011)
There are almost 390 healthcare services in Gaziantep and the medical waste quantity collected from these units is about 4000 kg per day. Healthcare services are consisted of hospitals, village clinics, policlinics, medicine centers, consulting rooms and etc. This study focuses on the examination information about the healthcare services and medical waste management strategies in Gaziantep. In this context, the number of healthcare services, medical waste quantities and the selected medical waste treatment options are determined.
Keywords: Medical waste; landfill; sterilization; Engineering